Optimizing Biochar Particle Size for Plant Growth and Mitigation of Soil Salinization - Esther Tang; Wenxi Liao; Sean C. Thomas (Agronomy, 2023)
Pyrolyzed waste biomass, or biochar, has been suggested as a means to increase plant growth and mitigate soil salinization, which is a widespread agricultural issue and can reach extreme levels in urban soils impacted by de-icing salts. Soil mixing is enhanced by reduced biochar particle size; however, biochar properties vary with particle size, and recent studies have suggested that plant growth responses may be maximized at intermediate particle sizes. We examined the responses of two plant species (cowpea (Vigna unguiculata) and velvetleaf (Abutilon theophrasti)) to biochar amendments that spanned a wide range of particle sizes obtained by sieving, with and without de-icing salt additions. The smallest size fractions of biochar reduced plant growth relative to unamended controls. Plant biomass production was generally maximized at intermediate biochar particle size treatments, with particle sizes of 0.5–2.0 mm showing the best response. Mitigation of salt effects was also improved at intermediate biochar particle sizes in this particle size range. Our results emphasize the importance of optimizing biochar particle size to best enhance plant responses to biochar, with particular reference to saline soils.